Bahasa Inggris - Annisa Nur Fitrihastuti; Natasya Meri Auliadani; Siti Mudrikah; Mutiara Tri Wulandari; Aisha Sayidinar; Arfista Deska Khairunnisa; Bunga Finovel Angellya; Laila Widi Utami; Ludmilla Fitri Untari (Fakultas Biologi Universitas Gadjah Mada, 2023)
Nglolang Beach located in Sepanjang street, Kemadang, Tanjungsari, Gunungkidul regency, Daerah Istimewa Yogyakarta, Indonesia. The substrate in this beach determines the presence of macroalgae. Macroalgae found in the intertidal zone, that is between sea and terrestrial environment. The characteristics of substrate in intertidal zones consist of sandy, rocky, and dead coral. Macroalgae plays the role of a producer for organisms in this ecosystem. Macroalgae also has an important role as a food source, bioremediation, a sink carbon, nutrient and energy, and economic benefits. This research aims to study about the abundance of macroalgae in the intertidal zone and the environmental factors that influence abundance of macroalgae at Nglolang Beach. The observation was conducted using a 1x1 m plot and the sampling using transect performed in the intertidal zone. The ecological parameters including water temperature and air temperature, salinity, and pH then being measured. After observation, the density (Ds), frequency (F), dominance (D), relative density (RD), relative frequency (RF), relative dominance (RDo) and Species important values index (IVI) were calculated. The highest importance value index belongs to the species Ulva lactuca (IVI = 93.84; RD = 36.28%; RF = 21.28%; RDo = 36.28%), meanwhile the lowest importance value belongs to the species Chaetomorpha crassa (IVI = 1.21; RD = 0.08%; RF = 1.06%; RDo = 0.08%).